Jezebel's war with America - Brown, Michael L., 1955- (FrontLine, 2019)
"Jezebel died 3,000 years ago. But her spirit lives today. Jezebel was the most wicked woman in the Bible, a powerful seductress who killed the prophets, led Israel into idolatry and immorality, and emasculated men. She was seductive and determined to snuff out the voices coming against her, because these voices were calling out for repentance. In twenty-first-century America, Jezebel is not a person. But it's as if the spirit of Jezebel is alive again today. The influence of the same demonic force is being felt in the massive increase of pornography and sexual temptation, the militant spirit of abortion, the rise of radical feminism, and most importantly, in the attempt to silence prophetic voices. Just as Jezebel clashed with strong men almost three thousand years ago, the demonic spirit of Jezebel is powerful in America, and it is going after the church. This eye-opening book not only unveils the satanic plot to destroy America, beginning with an all-out assault on the church, but it will equip every believer with tools to defeat the enemy in their own personal lives as well as in the nation. This book will show you how the spirit of Jezebel is active in America today and teach you how to protect the church"--